Improving Catalyst Activity in Hydrocarbon Functionalization by Remote Pyrene–Graphene Stacking. Issue 40 (24th May 2019) - Ballestin, Pilar; Ventura‐Espinosa, David; Martín, Santiago; Caballero, Ana; Mata, Jose A.; Pérez, Pedro J.
Abstract: A copper complex bearing an N ‐heterocyclic carbene ligand with a pyrene "tail" attached to the backbone has been prepared and supported on reduced graphene oxide (rGO). The free and supported copper materials have been employed as homogeneous and heterogeneous catalysts in the functionalization of hydrocarbons such as n ‐hexane, cyclohexane, and benzene through incorporation of the CHCO2 Et unit from ethyl diazoacetate. The graphene‐anchored complex displays higher reaction rates and induces higher yields than its soluble counterpart, features that can be rationalized in terms of a decrease in electron density at the metal center due to a remote net electronic flux from the supported copper complex to the graphene surface. Abstract : Electron density shifted to remote graphene : Anchoring an NHC‐Cu I complex onto graphene through a pyrene antenna (see graphic) enhances the catalytic properties of the copper center toward hydrocarbon functionalization by carbene transfer from ethyl diazoacetate.